Digital scholarship and the social network site: How academics conceptualise their networks on academic social network sites and Twitter - Jordan, Katy (AoIR Selected Papers of Internet Research, 2016)
Academic social networking sites (SNS) seek to bring the benefits of online networking to an explicitly academic audience. Currently, the two largest sites are Academia.edu and ResearchGate. The ability to make connections to others is a defining affordance of SNS; but what are the characteristics of the network structures being facilitated by academic SNS, and how does this relate to their professional use by academics? This study has sought to address this question through mixed methods social network analysis. Ego-networks were sampled from an academic SNS and Twitter for each participant. Academic SNS networks were smaller and more highly clustered; Twitter networks were larger and more diffuse. To understand the significance of the structures and how the networks were constructed, co-interpretive interviews were held with 18 participants. Annotating the networks revealed that communities are more frequently defined by institutions and research interests on academic SNS, compared to research interests and personal interests on Twitter. Emerging themes link network structure to differences in how academics conceptualise and use the sites. Academic SNS are regarded as a more formal academic identity, akin to a business card, or used as a personal repository. Twitter is viewed as a space where personal and professional are mixed, similar to a conference coffee break. Academic SNS replicate existing professional connections; Twitter reinforces existing professional relationships and fosters novel connections.